Agroforestry Systems for Carbon Sequestration: Present Status and Scope - Newaj, Ram; Dhyani, S.K. (Indian Journal of Agroforestry, 2020)
Climate change is the most severe problem that we are facing today in agriculture production and human health. C sequestration through agroforestry is a potential viable option to add trees on the farm lands, alone or in association with crops. The present forest cover is 20.68% of total Â Â geographical area and target fixed to increase tree cover to the extent of 33% by 2012 can only be achieved through agroforestry. Restoration of degraded lands has a tremendous potential for C sequestration, improving soil quality and increasing productivity through afforestation. Afforestation and reforestation are another viable option to increase carbon stocks in these pools. Substitution of fossil fuel has greatest mitigating potential in long term for which bio-fuel and ethanol production is the best options. This approach involves extending the production of bio-diesel through cultivation of tree bearing oil seed like jatropha, neem, karanj etc. and diversifies into the coproduction of ethanol by the sugar industries. The total potential of soil C sequestration in India is 92 Tg C yr-1, or about 30% of the fossil fuel emission. In addition, enhancement of soil quality can improve total food production by 6 to 12 million t yr-1. Trading C credits can provide additional income to the farmers and will encourage farmers to restore degraded soils and ecosystems. The paper presents potential and scope of agroforestry interventions as a means of sequestering C in soils and vegetation and mitigating global warming induced by green house effects.